Knowledge management alignment to the community of practice in a company of cutting and bending steel - de Barros Jerônimo, Taciana; Coutinho de Melo, Fagner José; Tomaz de Aquino, Joás; Gonzaga de Albuquerque, André Philippi; Dumke de Medeiros, Denise (Brazilian Journal of Operations & Production Management, 2018)
This article aims to analyze the characteristics of a community of practice focused on the quality of management decision making in a company in the metallurgical industry, which is a company of cutting and bending steel for construction. Quality management requires greater flexibility in the activities, information sharing, skills development of individuals, and engagement among employees. The scientific method adopted was the descriptive cross-analysis case study, whose data was collected through semi-structured interviews conducted with 180 individuals. It was observed that the creation of communities of practice does not occur at random, and its main features are defined identity of shared interest; the way to build the image belonging to a particular social group; and involvement in joint activities that allow them to learn from each other.